(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2022)
The Indonesian government conduct several strategies to enhance the SOE’s performance. However, some financial indicators show that reform program has not optimally achieved the objective to enhance the SOE performance. Therefore this paper is aimed to discuss some underlying factors that influence the SOE performance. As a result, the study found that contribution of Indonesia SOEs to economy is relatively low and stagnant. Besides that, many SOEs have not yet operated optimally. The regression result show the financial condition of the SOE is getting better when it have higher ability to generate profits and pay off debts. In addition, ability to pay off the debts is more important to maintain the financial performance of SOEs, than ability to generate profit. This study also indicate inefficiency in managing employee and policy formulation in Indonesia’s SOE.